PENGEMBANGAN HIGHER ORDER THINKING SKILL(HOTS) PADA SOAL PENILAIAN AKHIR SEMESTER GENAP MATA PELAJARAN IPAS SD - Dini Susanti; Ridania Ekawati; Arlina Yuza; Silfi Melidawati (PIONIR: JURNAL PENDIDIKAN, 2023)
The final even semester assessment questions are an assessment instrument used to evaluate the learning carried out by teachers and students during one semester. The aim of this research is to develop HOTS-based PAS questions so that students have a balance between attitude, knowledge and skills. The type of research used is research and development. The model used is the ADDIE model, which has five research stages. Namely analysis, design, development, implementation and evaluation. To test the validity of the product, it is tested by experts using a validity questionnaire, for practicality, a questionnaire is assessed by the teacher and an effectiveness questionnaire is assessed by the students. The results of this research show that the HOTS-based PAS IPAS questions meet the valid criteria of 81% in the very valid category, for practical results 96% in the very practical category and effectiveness results of 95% in the very valid category. So this HOTS-based PAS question reaches the criteria of being valid, practical and effective. Keywords: PAS questions, IPAS, HOTS, ADDIE